The Influence of Self-Efficacy and Work Environment on Teacher’s Professional Competence - Desiriani, Desiriani; Kristiawan, Muhammad; Wardiah, Dessy (Journal of Social Work and Science Education, 2023)
This study was conducted with the aim of testing 1) the magnitude of the influence of self-efficacy on the professional competence of teachers; 2) the magnitude of the influence of the work environment on the professional competence of teachers; and 3) the magnitude of the influence of self-efficacy and the work environment together on the professional competence of teachers. The method used in the implementation of this research is quantitative. The population and sample in this study were high school teachers in Lais District are SMAN 1 Lais, SMAN 2 Lais and SMAN 3 Lais. The results of the study stated that there was a positive and significant effect of self-efficacy and the work environment on the professional competence of teachers. In previous research, it examined more teacher’s performance factors as a focus of success. The novelty of this study is the focus on the success of quality education on teacher’s professional competence. The teacher’s professional competence needs serious attention from various parties, and efforts to increase factors related to teacher’s professional competence such as self-efficacy and work environment.